Menelusuri Jejak Kurikulum Pendidikan Imam Ghazali: Integrasi Ilmu Keislaman dalam Fiqih, Hadis, dan Bahasa Arab - Rahma Sekarningrum; Alfi Manzilatur Rohma; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2024)
The goal of this publication is to examine Imam Al-Ghazali's ideas about the curriculum, with a focus on how scientific and religious knowledge particularly Arabic should be integrated. Imam Al-Ghazali created a curriculum model that blends worldly knowledge with religious knowledge, particularly in the areas of fiqh, hadith, and Arabic, in order to create people who are not only intellectually gifted but also of noble character. Arabic plays a crucial part in this curriculum since it is the primary language used to comprehend the Koran and hadith, which form the foundation of Islamic beliefs. Understanding Islamic law correctly is based on Al-Ghazali's ideas regarding the significance of Arabic as the primary language for religious comprehension. Given the state of education today, a curriculum that incorporates religious understanding and